Studies on Utilization of Milk for Extraction of Polyphenols from Date Palm (Phoenix dactylifera L.). - Guhathakurta, Sampurna; Bandyopadhyay, Kakali; Chakraborty, Chaitali (Indian Journal of Dairy Science, 2017)
Abstract: Date palm is rich in phenolic compounds: flavonoids and phenolic acids. Flavonoids are not only potent antioxidants but also have a multitude of functional capabilities, which may have an effect on health. The objective of the present study is to increase the extraction of soluble polyphenols using milk as an extracting medium. The amount of soluble polyphenols present in date palm was measured in gallic acid equivalents using the Folin-Ciocalteau assay. For this purpose methanol, water and milk were utilized as extraction medium. For extraction of polyphenols with water and milk, four different temperatures were maintained which are room temperature (30â°C), 50â°C, 70â°C and 100â°C. Total phenolic content in gallic acid equivalents using Folin-Ciocalteau assay ranged from 21.15-68.95 milligrams of gallic acid equivalents per 100 gm date palm. It has been found that maximum extraction of polyphenols (76.3 mg of GAE/100 gm date palm) from date palm is obtained with milk at 70â°C which was even greater than methanol as extracting medium. It can be concluded that maximum amount of soluble polyphenols was achieved when consumed with hot milk at 70â°C.